Types and Branches of Tadlīs (Misrepresentation) in Ḥadīth: An Applied Study - Al Ghouri, Syed Abdul Majid (Journal of Islamic and Religious Studies, 2021)
‘Ulūm al Ḥadīth (i.e., sciences of Ḥadīth) are considered one of the noblest Islamic sciences because they give the learner aware about the principles necessary for accepting or rejecting Ḥadīth based on the status of sanad (line of narrators) and matn (narrated text). Through these sciences, Ṣaḥīḥ and Ḍa’īf of Sunnah can be known. One of the important topics of these sciences (through which a judgment can be made whether sanad is muttasil (i.e., thoroughly connected) or mursal, and then knowing that Ḥadīth is Ṣaḥīh or Ḍa’īf is called Tadlīs which refers, as per the nomenclature of Ḥadīth scholars, on narrator’s hiding a defect in sanad and improve its apparent view. Hence, this type is considered one of the most delicate and important types of Ḥadīth sciences because it contains cover-up, ambiguousness, illusion and disguise. Whoever wrote, in the past or present, about scholars of Ḥadīth had discussed about tadlīs and its types. However, discussion in their books was concise and very short so the readers do not get a comprehensive and clear picture of the same. Further, their discussion did not introduce all types and branches of tadlīs with illustrative examples. This research presents a brief study on tadlīs highlighting its main aspects, introducing its main types and branches with illustrative examples to each of them and giving the judgement for each of them. The researcher applied inductive and analytical research approaches in the study. Inductive approach was aimed to collect information about tadlīs and its types from the classical and modern resources of Ḥadīth sciences. Analytical approach was applied in analyzing views of some scholars in this type, sections and branches.